Harnessing Artificial Intelligence for Youth Engagement in Agriculture: Lessons from Global Practices and Prospects for Nigeria - Oluwatoyin Olatunde Olagunju (MultiTech Publisher, 2024)
The demand for sustainable farming techniques is growing as the world's population rises. In light of this requirement, enlisting young people in agriculture becomes an essential tactic for guaranteeing food security, economic growth, and rural rejuvenation. Using artificial intelligence (AI) offers a viable way to empower and draw young people to the agriculture industry. This study explores the possibilities for Nigeria while providing a summary of international approaches to using AI to encourage youth involvement in agriculture. By utilizing AI technologies like machine learning, remote sensing, and data analytics, youth can access valuable insights, optimize resource utilization, and mitigate risks associated with agricultural production. In conclusion, this paper emphasizes how AI might inspire young people to pursue careers in agriculture and emphasizes the necessity of developing methods specifically designed to maximize AI's potential in Nigeria. Nigeria can set the stage for a sustainable and inclusive agricultural future by encouraging stakeholder engagement, investing in digital infrastructure, and advancing creative policies. This would enable the country's young to spearhead agricultural transformation and economic success.